Developing a Genre-Based ESP English Module for Vocational Accounting Students - Puspasari, Rini; Hawanti, Santhy (Universitas Jambi, Magister Program of English Education Department, 2026)
Preparing vocational students for workplace communication has become an important objective of English language education. However, English instruction for vocational accounting students remains predominantly based on general English materials that inadequately address their workplace communication needs. Although previous studies have investigated English for Specific Purposes (ESP), Genre-Based pedagogy, or instructional material development, few have integrated these components into a systematic instructional framework for vocational accounting education. This Research and Development (R&D) study aimed to identify vocational accounting students’ English language needs, develop an ESP-based English module through a Genre-Based Approach, and evaluate the validity, practicality, and effectiveness. The study adopted the ADDIE instructional design model and involved 30 Grade XI Accounting and Financial Institution students at a vocational high school in Indonesia. Data were collected through questionnaires, interviews, document analysis, classroom observations, expert validation, learning achievement tests, and response questionnaires. The findings revealed that students required contextualized English materials emphasizing accounting-related communication, professional vocabulary, authentic workplace tasks, and scaffolded learning activities. The developed module consisted of five genre-based units organized into two integrated skill clusters. Expert validation indicated that the module was highly valid, while classroom implementation showed highly positive student responses and improved students’ learning achievement. This study presents an integrated instructional framework that combines ESP, learners’ needs analysis, Genre-Based pedagogy, and the ADDIE model to support workplace-oriented English learning in vocational accounting education.